P291 Long-term use of glucocorticoids for polymyalgia rheumatica: follow-up of the PMR cohort study. (23rd April 2022) - Muller, Sara; Hider, Samantha L; Sokhal, Balamrit Singh; Lawton, Sarah A; Helliwell, Toby; Mallen, Christian D
Abstract: Background/Aims: Polymyalgia rheumatica (PMR) is a common inflammatory rheumatological condition in older adults, characterised by pain and stiffness in the shoulder and hip girdles. The mainstay of treatment is oral glucocorticoids (GCs). Classically, treatment is tapered to a stop over two years, but there is growing evidence this does not happen in practice. International guidelines recommend early referral to specialist services for patients at risk of prolonged treatment. However, they do not specify who these patients are. This study considers the factors at, and shortly after, diagnosis that might be associated with prolonged glucocorticoid treatment, and therefore who may benefit from early specialist review. Methods: 652 people with incident PMR were recruited from English general practice between 2012 and 2014. They completed up to seven questionnaires over two years and a further long-term follow-up questionnaire (LTFUQ) 4.5-6.5 years after diagnosis. The first seven questionnaires have previously been used to allocate people to pain-stiffness trajectory classes. In the LTFUQ, participants reported current symptoms and other general health and lifestyle characteristics, as well as whether they were still taking GCs and whether they self-managed their GC use. Characteristics of those having successfully stopped GCs were compared to those still taking them. Results: A median 5.16 years after diagnosis, 179 people responded to the LTFUQ. Of these, 67 (40.1%) were still on GCs with a mean daily dose of 5mg (1.5, 9). Those still taking GCs were more likely to be older (72.5 vs 70.2 years, p = 0.035), to live alone (31.8% v 15.0%, p = 0.01), and to report having self-managed their GCs (39.1% versus 11.0%, p < 0.0001). They were also more likely to have reported sustained pain-stiffness symptoms in the first two years, as defined by their trajectory class in earlier work (trajectory class [n{%} still treated]; partial recovery, sustained moderate symptoms [23 {34.3%}]; recovery before worsening [17 {25.4%}]; rapid and sustained recovery [15 {22.4%}]; Slow and continuous recovery [11 {16.34%}]). Conclusion: PMR is not always the typically-described, time-limited condition. There are few patient characteristics that are associated with prolonged treatment early in the disease course, but those who are older and have sustained or recurrent pain and stiffness over two years appear to be at greater risk of remaining on GCs. Whilst accurate prediction of long-term treatment need is not possible from our data, people with sustained symptoms may benefit from specialist review to ensure diagnostic accuracy and consider need for additional therapies to reduce their GC burden. Disclosure: S. Muller: None. S.L. Hider: None. B. Singh Sokhal: None. S.A. Lawton: None. T. Helliwell: None. C.D. Mallen: None.